SOME SUPER EDGE-MAGIC TOTAL LABELINGS OF THE TREE GRAPH T A,C,D - SURYADI, IYAN
Let G = (V (G), E (G) ) be a simple and finite graph with the vertex-set V (G) and the edge-set E (G). An edge-magic total labeling of a graph G is an injective function f from V (G) U E (G) ke {1,2,3, ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â… , |V (G) | + |E (G) |} such that there exists a positive integer k satisfying f (u) + f (uv) + f (v) = k for each uv E E(G). A graph having an edge-magic total labeling is called a total edge-magic graph. In this case, if f (V(G)) = {1,2,3, ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â… , |V (G)|}, then f is called a super edge-magic total labeling of G and G is called a super edgemagic total graph.